Is the prevalence of mental illness increasing in Australia? Evidence from national health surveys and administrative data, 2001–2014 - Harvey, Samuel B; Deady, Mark; Wang, Min‐Jung; Mykletun, Arnstein; Butterworth, Peter; Christensen, Helen; Mitchell, Philip B (Medical journal of Australia, 2017)
Objectives: To assess changes in the prevalence rates of probable common mental disorders (CMDs) and in rates of disability support pensions (DSPs) for people with psychiatric disorders in Australia between 2001 and 2014. Design, setting and participants: Secondary analysis of data from five successive Australian national health surveys of representative samples of the working age population (18–65 years of age) and national data on DSP recipients. Main outcome measures: Prevalence of probable CMDs with very high symptom level (defined by a Kessler Psychological Distress Scale [K10] score of 30 or more) or with high symptom level (K10 score of 22 or more); the proportion of working age Australians receiving DSPs for psychiatric conditions. Results: There was no change in the prevalence rate of probable CMDs with very high symptom levels between 2001 and 2014, but a slight decrease in the prevalence of probable CMDs with high symptoms levels, particularly among those under 45 years of age. Over the same period, the proportion of working age individuals receiving DSPs for psychiatric conditions increased by 51% (for trend, P < 0.001), equivalent to one additional DSP for every 182 working age Australians. Conclusions: Contrary to popular belief, the prevalence of probable CMDs in Australia was stable between 2001 and 2014. However, the proportion of the working age population receiving DSPs for psychiatric conditions increased dramatically over the same period. This conundrum is a major public health problem that should be further examined.